A Unique Presentation of Concomitant Hypo-Hyperdontia in Seven Year Old Child: A Rare Report - Mallineni, Sreekanth K.; Mohiuddin, Azher; Patil, Anil K.; Kodali, Ranvitha P. (Journal of Dentistry Indonesia, 2015)
Numerical variations of teeth are common. Hypodontia considered being presence of less number of teeth in normal complement while extra teeth to normal dentition are considered as hyperdontia. Hypodontia and hyperdontia are two opposite numerical variations of human dentition and occurrence of these two conditions is called as concomitant hypo-hyperdontia. The occurrence of hypo-hyperdontia in a patient is common. This report describes a rare occurrence of conical shape supernumerary teeth in premolar region and agenesis of tooth 55 and 81 in primary dentition and teeth 15, 25 and 41 in permanent dentition.